Analisis Ketepatan Kode Diagnosis Utama Kasus Persalinan Sebelum dan Sesudah Verifikasi pada Pasien BPJS di Rsup Dr. Soeradji Tirtonegoro Klaten - Nandani Kusuma Ningtyas; Sri Sugiarsi; Astri Sri Wariyanti (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background: Based on the preliminary survey at RSUP dr. Soeradji Tirtonegoro Klaten found the main diagnosis code differences in 5 out of 10 BPJS patient medical record for labor cases before and after verification.Objective: To determine the accuracy of the main diagnosis codes of labor cases before and after verification in BPJS patients at dr. Soeradji Tirtonegoro KlatenGeneral Hospital.Methods: Type of research is comparative analytic with cross sectional approach. The population is medical record of JKN BPJS inpatients in the first quarter of 2017. The samples are 50 documents use systematic sampling technique. The instrument is checklist and list of questions. Collecting data use observation and unstructured interviews. Data processing use collecting, editing, coding, entering, processing, cleaning and presenting data. Data analysis used Fisher exact test.Results: The accuracy of the main diagnosis codes of labor cases before verification is 25 (50%) correct and 25 (50%) incorrect. The accuracy of the main diagnosis code for labor cases after verification is 29 (58%) correct and 21 (42%) incorrect. The results of Fisher exact test were obtained p value (0.274)> 0.05.Conclusion : There is no difference in the accuracy of the main diagnosis codes of labor cases before and after verification in BPJS patients. It is recommended in determining the main diagnosis code based on the coding rules in ICD-10 and the internal verifier still check the diagnosis code.